EFL teachers’ reasons for selecting instructional materials during the COVID-19 pandemic - Suharyadi Suharyadi; Anik Nunuk Wulyani (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
EFL teachers’ reasons for selecting instructional materials during the COVID-19 pandemicThe COVID-19 pandemic has changed how teachers teach and students learn in the classroom. One of the challenges in the online teaching is that teachers are required to prepare the instructional materials for their students. This study aims at investigating the EFL teachers’ reasons for choosing the instructional materials in the time of the COVID-19 pandemic. By employing a set of questionnaires, this study collected the data from 219 English teachers from various levels of education online via the google form link. The data collection was done for one month starting from 5 May to 5 June 2020. The data were analyzed through a content analysis by identifying, grouping, and categorizing similar and different responses. The results of analysis showed that the EFL teachers have five categories of reasons in selecting the instructional materials in the time of pandemic: the instructional materials should be easy, relevant, simple, attractive, and absent from crime, pornography, and viruses. These results suggest that the EFL teachers make use of these reasons in selecting and developing the instructional materials for their students during and after the pandemic. For future textbook developers, these considerations can be used a reference to develop textbooks which accommodate students’ voices and teachers’ voices during the online teaching and learning activities.Keywords: EFL, teachers, reasons, instructional materials, COVID-19Alasan-alasan guru bahasa Inggris sebagai bahasa asing dalam memilih materi pembelajaran selama pandemi COVID-19Pandemi COVID-19 telah banyak mengubah bagaimana guru mengajar dan siswa belajar di dalam kelas. Salah satu tantangan dalam pembelajaran daring adalah guru harus menyiapkan materi pembelajaran untuk siswa. Penelitian ini bertujuan untuk menginvestigasi alasan-alasan guru bahasa Inggris dalam memilih materi pembelajaran selama masa pandemi COVID-19. Dengan memanfaatkan angket sebagai instrumen penelitian, data dikumpulkan dari 219 guru bahasa Inggris yang berasal dari berbagai tingkat satuan pendidikan. Angket didistribusikan kepada para guru secara daring mulai tanggal 5 Mei sampai 4 Juni 2020. Konten respon guru bahasa Inggris kemudian dianalisis dengan mengidentifikasi, mengelompokkan, dan mengkategorikan jawaban-jawaban yang sama dan berbeda. Hasil analisis menujukkan bahwa guru bahasa Inggris memiliki lima alasan dalam memilih materi pembelajaran selama pandemi COVID-19: materi pembelajaran harus mudah, relevan, sederhana, menarik, dan aman dari unsur kriminal, pornografi, dan virus. Berdasarkan hasil ini, guru bahasa Inggris disarankan menggunakan lima alasan ini dalam pemilihan dan pengembangan materi pembelajaran selama dan setelah pandemi COVID-19. Selain itu, pengembang buku ajar juga disarankan menggunakan hasil ini sebagai referensi dalam mengembangkan buku ajar yang mengakomodasi perspektif para guru dan siswa.Kata kunci: bahasa Inggris, guru, alasan, materi pembelajaran, COVID-19